ZnO-based voltage-sensitive ceramic preparation method based on heat treatment assisted cold sintering
Through the heat treatment-assisted cold sintering process, the problems of high energy consumption and excessive grain growth in traditional high-temperature sintering processes are solved, and the preparation of high-performance ZnO-based pressure-sensitive ceramics is realized, with excellent electrical properties and high density.
Patent Information
- Application Number
- CN202411946757.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Traditional high-temperature sintering processes lead to high energy consumption and excessive growth of ceramic grains, reducing material density and mechanical properties. At the same time, multiple groups of distributors are prone to adverse chemical reactions in high-temperature environments, affecting the pressure sensitive performance and long-term stability of ceramics.
The heat treatment-assisted cold sintering process is adopted to perform preliminary densification by applying pressure at low temperatures, and then the microstructure of the ceramic is further optimized at a heat treatment temperature of 800-950°C, and the sintering temperature is reduced to below 900°C.
It significantly reduces energy consumption, improves the relative density and electrical properties of ceramics, has a pressure sensitivity coefficient of 92, and a breakdown strength of 1600V/mm, surpassing the performance of commercial resistor plates.
Smart Images

Figure CN119859055A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing ZnO ceramics, and in particular to a method for preparing ZnO-based varistor ceramics by heat treatment-assisted cold sintering. Technical Background
[0002] ZnO-based varistors are widely used in high-voltage resistors and gas sensors, but their preparation process faces many technical challenges. The traditional high-temperature sintering process usually needs to be carried out at around 1100°C, which not only leads to high energy consumption, but also causes excessive growth of ceramic grains, significantly reducing the density and mechanical properties of the material. In addition, multi-component formulations of ZnO-based ceramics, such as Bi2O3, Mn2O3, NiO, SnO2, In2O3, CaO and Dy2O3, are prone to adverse chemical reactions or transitional volatilization in high-temperature environments, thereby affecting the varistor performance and long-term stability of the ceramics. At present, common problems of commercial varistors include low varistor coefficients (usually between 30 and 50) and low breakdown strength (about 400V / mm), which limits their further development in high-performance applications. Therefore, exploring new preparation processes and optimizing ZnO-based ceramic formulations have become key ways to improve their performance.
[0003] In order to solve the shortcomings of traditional high-temperature sintering processes and improve the overall performance of ceramics, cold sintering technology has gradually attracted attention. Cold sintering achieves initial densification of ceramics by applying pressure at a relatively low temperature (usually ≤300°C). Compared with high-temperature sintering, cold sintering can significantly reduce energy consumption (only about 1% of traditional sintering), and effectively control grain growth, reduce component volatilization, and maintain the uniformity of ceramic composition. For example, by controlling the sintering temperature between 120°C and 300°C, cold sintering can achieve a density of more than 90% for ceramics. However, despite the excellent performance of cold sintering in reducing temperature and energy saving, the ceramic materials prepared by it still have deficiencies in density and electrical properties. This is because at low temperatures, most inorganic doping phases cannot achieve effective synergistic sintering, and there is a lack of sufficient nucleation driving force during the dissolution-precipitation process, resulting in the formation of a large amount of amorphous phases at the grain boundaries, which seriously affects the electrical properties of electrical ceramic materials. Secondly, the "dissolution-precipitation" process in the cold sintering step will form an interface layer that wraps the grains, hindering the formation of grain boundaries and thus deteriorating the varistor properties. Although the ZnO varistor ceramics prepared by the traditional solid-phase method have good density, the high temperature environment (≥1100°C) required for sintering will lead to the coarsening of the grains, which will reduce the proportion of high-insulation grain boundaries and make it difficult to obtain high breakdown strength performance. Therefore, on the basis of the existing cold sintering process, it is particularly important to further optimize the formula and process parameters, especially in improving the varistor coefficient and breakdown strength of the ceramic. This also provides a new research direction and practical path for the development of high-performance ZnO-based varistor ceramics. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing high-performance ZnO-based varistor ceramics based on heat treatment-assisted cold sintering. Compared with the sintering temperature of up to 1100°C in the traditional solid phase method, the present invention can significantly reduce the sintering temperature to below 900°C, and the relative density of the prepared ZnO-based varistor ceramic material is as high as 99%, and it also has excellent electrical properties (varistor coefficient up to 92, breakdown strength up to 1600V / mm). The method of the present invention not only has significant advantages in energy conservation and emission reduction, but also can significantly improve the electrical properties of ceramics, surpassing the performance of general commercial resistors.
[0005] The technical solution adopted by the present invention to solve the above technical problems is:
[0006] A method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering, the method comprising the following steps:
[0007] S1: prepare a citric acid solution with deionized water and citric acid, wherein the concentration of the citric acid solution is 0.5-4 mol%.
[0008] S2: mixing the initial ZnO powder with a metal oxide dopant to form a precursor powder, wherein the metal oxide dopant accounts for 0-9.2 wt % of the total mass of the initial ZnO powder.
[0009] S3: Mix the precursor powder prepared in S2 with the citric acid solution, grind and disperse to obtain a mixed slurry, wherein the amount of the citric acid solution added is 50-100wt% of the mass of the precursor powder.
[0010] S4: Put the mixed slurry into a steel mold, apply a pressure of 50-300MPa, and cold sinter at 150-300℃ for 0.5-2h.
[0011] S5: heat treating the cold sintered sample at a temperature ranging from 800 to 950°C for a holding time of 0.5 to 4 hours, and finally obtaining a high-performance ZnO-based varistor ceramic.
[0012] As an improvement, the metal oxide dopant is one or more of Bi2O3, Mn2O3, NiO, SnO2, In2O3, and CaO metal oxides.
[0013] As an improvement, when the metal oxide dopant is composed of multiple metal oxides, each metal oxide accounts for 0.3-3 wt % of the total mass of the initial ZnO powder.
[0014] Compared with the prior art, the present invention has at least the following advantages:
[0015] (1) The method for preparing high-performance ZnO-based varistor ceramics based on heat treatment assisted cold sintering of the present invention has a simple process and low energy consumption, which effectively reduces the energy consumption of traditional high-temperature sintering processes.
[0016] (2) The heat treatment auxiliary process of the present invention can eliminate the internal stress and residual amorphous phase in the cold sintered sample, and transform the interface layer left after cold sintering into a high-resistance grain boundary, thereby significantly enhancing the grain boundary characteristics of the ceramic. This is not only conducive to maintaining the microstructural stability of the ceramic, but also greatly enhances the electrical properties. The ZnO-based varistor ceramics prepared by this process far exceed the varistor ceramics prepared by single cold sintering or traditional solid-phase sintering in terms of non-ohmic properties and electrical breakdown strength.
[0017] (3) The present invention effectively avoids abnormal growth of ceramic grains and significantly reduces porosity by combining cold sintering and heat treatment at a temperature about 300°C lower than the traditional high-temperature sintering temperature, thereby achieving densification of the ceramic with a relative density greater than 99%.
[0018] (4) The optimized formula process proposed in the present invention is equally important for improving the nonlinear coefficient (up to 92) and breakdown strength (reaching 1600V / mm) of ZnO-based varistor ceramics. The ZnO resistor prepared by the heat treatment assisted cold sintering process has broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Flow chart of preparing ZnO-based varistor ceramics by heat treatment assisted cold sintering according to an embodiment.
[0020] Figure 2 Grain morphology under different heat treatment temperature conditions.
[0021] Figure 3 The grain boundary morphology before and after heat treatment.
[0022] Figure 4 Figure 2 is a graph of actual density and relative density under different heat treatment temperature conditions.
[0023] Figure 5 JE curves under different heat treatment temperature conditions. DETAILED DESCRIPTION
[0024] The present invention is described in further detail below.
[0025] The heat treatment assisted cold sintering technology adopted in the present invention realizes efficient low-temperature sintering of ZnO-based varistor ceramics by setting a specific concentration and addition amount of citric acid solution during the cold sintering process. This process can preliminarily achieve the densification of ceramics under a temperature of 300°C by applying appropriate pressure and controlling time, and further improve the density and electrical properties of the material during the heat treatment process of 800°C to 950°C. Compared with the sintering temperature of up to 1100°C in traditional high-temperature sintering, this method can significantly reduce the sintering temperature by about 300°C, greatly saving energy. The core of this technology is to promote the uniform dispersion of ZnO-based powder through the local wetting effect of citric acid, and gradually realize the densification of grains under low temperature conditions. Subsequently, the microstructure of the ceramic is further optimized by heat treatment, so that it has excellent varistor coefficient and breakdown strength.
[0026] The present invention adopts heat treatment assisted cold sintering technology to prepare high-performance ZnO-based varistor ceramics. The results show that ZnO-based ceramics can achieve preliminary densification under 300°C and 100MPa pressure conditions by using 4mol% concentration and 50-100wt% mass fraction of citric acid solution, and the relative density after cold sintering is higher than 88%. After heat treatment at 800°C to 950°C, the relative density of the ceramic can be further increased to more than 95%, and the relative density of the cold sintered sample assisted by 870°C heat treatment can reach 99% and the grain size is only 1.75μm, which is better than the samples prepared by the traditional solid phase method. Electrical performance tests show that the breakdown strength of the ZnO-based varistor ceramics prepared by heat treatment assisted cold sintering technology is as high as 1600V / mm, and the nonlinear varistor coefficient is as high as 92, which is far beyond the current commercial level.
[0027] Embodiment 1, a method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering, the process steps of which include:
[0028] (1) Prepare a 0.5 mol% citric acid solution using deionized water and glacial citric acid.
[0029] (2) Cold sintering: The ZnO initial powder was mixed with 50 wt% citric acid solution, and the mixed slurry was obtained after grinding and dispersion. The mixed slurry was then placed in a steel mold, a pressure of 50 MPa was applied, and cold sintering was performed at 300° C. for 2 hours.
[0030] (3) Heat treatment assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 800°C at a heating rate of 1°C / min for 0.5 h to obtain ZnO varistor ceramics.
[0031] (4) The test results are as follows:
[0032] Relative density (%) Grain size (μm) Breakdown strength (V / mm) Nonlinear coefficient 93 1.48 3200 0.03
[0033] Embodiment 2, a method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering, the process steps of which include:
[0034] (1) Prepare a 1 mol% citric acid solution using deionized water and glacial citric acid.
[0035] (2) Cold sintering: The ZnO initial powder was mixed with 50 wt% citric acid solution, and a mixed slurry was obtained after grinding and dispersion. The mixed slurry was then placed in a steel mold, a pressure of 50 MPa was applied, and cold sintering was performed at 200° C. for 1 hour.
[0036] (3) Heat treatment assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 800°C at a heating rate of 1°C / min for 0.5 h to obtain ZnO varistor ceramics.
[0037] (4) The test results are as follows:
[0038] Relative density (%) Grain size (μm) Breakdown strength (V / mm) Nonlinear coefficient 96 1.92 2600 0.03
[0039] Embodiment 3, a method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering, the process steps of which include:
[0040] (1) Prepare a 1 mol% citric acid solution using deionized water and glacial citric acid.
[0041] (2) Cold sintering: The initial ZnO powder was mixed with 3 wt% Bi2O3 doping amount, and then mixed with 70 wt% citric acid solution. After grinding and dispersion, a mixed slurry was obtained. The mixed slurry was then placed in a steel mold, a pressure of 300 MPa was applied, and cold sintering was performed at 150°C for 2 hours.
[0042] (3) Heat treatment assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 950°C at a heating rate of 3°C / min for 4 hours to obtain ZnO varistor ceramics.
[0043] (4) The test results are as follows:
[0044] Relative density (%) Grain size (μm) Breakdown strength (V / mm) Nonlinear coefficient 94 3.65 750 5
[0045] Embodiment 4, a method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering, the process steps of which include:
[0046] (1) Prepare a 2 mol % citric acid solution using deionized water and glacial citric acid.
[0047] (2) Cold sintering: The initial ZnO powder was mixed with 2wt% Bi2O3 and 1wt% Mn2O3 doping amounts, and then mixed with 100wt% citric acid solution. The mixed slurry was obtained after grinding and dispersion. The mixed slurry was then placed in a steel mold, a pressure of 200MPa was applied, and cold sintering was performed at 250°C for 0.5 hours.
[0048] (3) Heat treatment assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 950°C at a heating rate of 10°C / min for 4 hours to obtain ZnO varistor ceramics.
[0049] (4) The test results are as follows:
[0050] Relative density (%) Grain size (μm) Breakdown strength (V / mm) Nonlinear coefficient 94 2.43 940 9
[0051] Embodiment 5, a method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering, the process steps of which include:
[0052] (1) Prepare a 2.5 mol% citric acid solution using deionized water and glacial citric acid.
[0053] (2) Cold sintering: The initial ZnO powder was mixed with 0.3wt% Bi2O3, 3wt% Mn2O3, 0.5wt% NiO, and 1wt% SnO2 doping amounts, and then mixed with 100wt% citric acid solution. The mixed slurry was obtained after grinding and dispersion. The mixed slurry was then placed in a steel mold, a pressure of 200MPa was applied, and cold sintering was performed at 200°C for 2 hours.
[0054] (3) Heat treatment assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 800 °C at a heating rate of 3 °C / min for 2 h to obtain ZnO varistor ceramics.
[0055] (4) The test results are as follows:
[0056] Relative density (%) Grain size (μm) Breakdown strength (V / mm) Nonlinear coefficient 96 1.13 6800 10
[0057] Embodiment 6, a method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering, the process steps of which include:
[0058] (1) Prepare a 4 mol% citric acid solution using deionized water and glacial citric acid.
[0059] (2) Cold sintering: The initial ZnO powder was mixed with 3wt% Bi2O3, 1wt% Mn2O3, 1wt% NiO, and 1wt% SnO2, and then mixed with 100wt% citric acid solution. The mixed slurry was obtained after grinding and dispersion. The mixed slurry was then placed in a steel mold, a pressure of 100MPa was applied, and cold sintering was performed at 300°C for 1 hour.
[0060] (3) Heat treatment assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 850°C at a heating rate of 3°C / min and kept at this temperature for 2 h to obtain ZnO varistor ceramics.
[0061] (4) The test results are as follows:
[0062] Relative density (%) Grain size (μm) Breakdown strength (V / mm) Nonlinear coefficient 97 1.38 3200 20
[0063] Embodiment 7, a method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering, the process steps of which include:
[0064] (1) Prepare a 4 mol% citric acid solution using deionized water and glacial citric acid.
[0065] (2) Cold sintering: The initial ZnO powder was mixed with 3wt% Bi2O3, 0.3wt% Mn2O3, 0.5wt% NiO, 1wt% SnO2, 0.3wt% In2O3, and 0.7wt% CaO, and then mixed with 100wt% citric acid solution. The mixed slurry was obtained after grinding and dispersion. The mixed slurry was then placed in a steel mold, a pressure of 100MPa was applied, and cold sintering was carried out at 300°C for 2 hours.
[0066] (3) Heat treatment assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 870°C at a heating rate of 3°C / min and kept at this temperature for 2 hours to obtain ZnO varistor ceramics.
[0067] (4) The test results are as follows:
[0068] Relative density (%) Grain size (μm) Breakdown strength (V / mm) Nonlinear coefficient 99 1.75 1600 92
[0069] Embodiment 8, a method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering, the process steps of which include:
[0070] (1) Prepare a 3 mol% citric acid solution using deionized water and glacial citric acid.
[0071] (2) Cold sintering: The initial ZnO powder was mixed with 3 wt% Bi2O3, 2 wt% Mn2O3, 0.5 wt% NiO, 1 wt% SnO2, 0.3 wt% In2O3, and 0.3 wt% CaO, and then mixed with 100 wt% citric acid solution. The mixed slurry was obtained after grinding and dispersion. The mixed slurry was then placed in a steel mold and a pressure of 200 MPa was applied. Cold sintering was performed at 200°C for 2 hours.
[0072] (3) Heat treatment assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 900 °C at a heating rate of 3 °C / min for 2 h to obtain ZnO varistor ceramics.
[0073] (4) The test results are as follows:
[0074] Relative density (%) Grain size (μm) Breakdown strength (V / mm) Nonlinear coefficient 97 2.24 1000 60
[0075] Embodiment 9, a method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering, the process steps of which include:
[0076] (1) Prepare a 3 mol% citric acid solution using deionized water and glacial citric acid.
[0077] (2) Cold sintering: The initial ZnO powder was mixed with 3wt% Bi2O3, 1wt% Mn2O3, 0.5wt% NiO, 1wt% SnO2, 3wt% In2O3, and 0.7wt% CaO, and then mixed with 100wt% citric acid solution. The mixed slurry was obtained after grinding and dispersion. The mixed slurry was then placed in a steel mold and a pressure of 100 MPa was applied. Cold sintering was performed at 300°C for 2 hours.
[0078] (3) Heat treatment assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 900 °C at a heating rate of 3 °C / min for 3 h to obtain ZnO varistor ceramics.
[0079] (4) The test results are as follows:
[0080] Embodiment 10, a method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering, the process steps of which include:
[0081] (1) Prepare a 4 mol% citric acid solution using deionized water and glacial citric acid.
[0082] (2) Cold sintering: The initial ZnO powder was mixed with 2wt% Bi2O3, 1wt% Mn2O3, 3wt% NiO, 1wt% SnO2, 0.3wt% In2O3, and 0.7wt% CaO, and then mixed with 100wt% citric acid solution. The mixed slurry was obtained after grinding and dispersion. The mixed slurry was then placed in a steel mold and a pressure of 100 MPa was applied. Cold sintering was performed at 300°C for 2 hours.
[0083] (3) Heat treatment assistance: The cold sintered sample was transferred into a muffle furnace and heated to 40°C at a heating rate of 1°C / min.
[0084] Relative density (%) Grain size (μm) Breakdown strength (V / mm) Nonlinear coefficient 94 2.88 850 35
[0085] 880℃, holding time is 2.5 hours, then ZnO varistor ceramics are obtained.
[0086] (4) The test results are as follows:
[0087] Relative density (%) Grain size (μm) Breakdown strength (V / mm) Nonlinear coefficient 96 2.12 1400 54
[0088] Embodiment 11, a method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering, the process steps of which include:
[0089] (1) Prepare a 4 mol % citric acid solution using deionized water and glacial citric acid.
[0090] (2) Cold sintering: The initial ZnO powder was mixed with 2wt% Bi2O3, 1wt% Mn2O3, 3wt% SnO2, and 0.7wt% CaO, and then mixed with 60wt% citric acid solution. The mixed slurry was obtained after grinding and dispersion. The mixed slurry was then placed in a steel mold, a pressure of 100MPa was applied, and cold sintering was performed at 300°C for 0.5 hours.
[0091] (3) Heat treatment assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 830°C at a heating rate of 1°C / min for 1.5 hours to obtain ZnO varistor ceramics.
[0092] (4) The test results are as follows:
[0093] Relative density (%) Grain size (μm) Breakdown strength (V / mm) Nonlinear coefficient 96 1.22 3460 20
[0094] Embodiment 12, a method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering, the process steps of which include:
[0095] (1) Prepare a 4 mol % citric acid solution using deionized water and glacial citric acid.
[0096] (2) Cold sintering: The initial ZnO powder was mixed with 3wt% Bi2O3, 1wt% Mn2O3, 0.5wt% NiO, and 3wt% CaO, and then mixed with 80wt% citric acid solution. The mixed slurry was obtained after grinding and dispersion. The mixed slurry was then placed in a steel mold, a pressure of 100MPa was applied, and cold sintering was performed at 300°C for 2 hours.
[0097] (3) Heat treatment assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 880°C at a heating rate of 7°C / min for 1.5 hours to obtain ZnO varistor ceramics.
[0098] (4) The test results are as follows:
[0099] Relative density (%) Grain size (μm) Breakdown strength (V / mm) Nonlinear coefficient 98 1.42 2460 32
[0100] Embodiment 13, a method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering, the process steps of which include:
[0101] (1) Prepare a 4 mol % citric acid solution using deionized water and glacial citric acid.
[0102] (2) Cold sintering: The initial ZnO powder was mixed with 3wt% Bi2O3, 0.5wt% NiO, 0.3wt% SnO2, and 0.7wt% CaO, and then mixed with 80wt% citric acid solution. The mixed slurry was obtained after grinding and dispersion. The mixed slurry was then placed in a steel mold, a pressure of 100MPa was applied, and cold sintering was performed at 300°C for 2 hours.
[0103] (3) Heat treatment assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 920°C at a heating rate of 7°C / min for 0.5 h to obtain ZnO varistor ceramics.
[0104] (4) The test results are as follows:
[0105] Relative density (%) Grain size (μm) Breakdown strength (V / mm) Nonlinear coefficient 97 3.12 860 12
[0106] Embodiment 14, a method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering, the process steps of which include:
[0107] (1) Prepare a 4 mol % citric acid solution using deionized water and glacial citric acid.
[0108] (3) Cold sintering: The initial ZnO powder was mixed with 3wt% Bi2O3, 1wt% Mn2O3, 0.5wt% NiO, 1wt% SnO2, 1wt% In2O3, and 0.7wt% CaO, and then mixed with 80wt% citric acid solution. The mixed slurry was obtained after grinding and dispersion. The mixed slurry was then placed in a steel mold, a pressure of 100MPa was applied, and cold sintering was carried out at 300°C for 2 hours.
[0109] (3) Heat treatment assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 950 °C at a heating rate of 5 °C / min for 3.5 h to obtain ZnO varistor ceramics.
[0110] (4) The test results are as follows:
[0111] Relative density (%) Grain size (μm) Breakdown strength (V / mm) Nonlinear coefficient 98 3.42 780 35
Claims
1. A method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering, characterized in that: The method comprises the following steps: S1: preparing a citric acid solution with deionized water and citric acid, wherein the concentration of the citric acid solution is 0.5-4 mol%; S2: mixing the initial ZnO powder with a metal oxide dopant to form a precursor powder, wherein the metal oxide dopant accounts for 0-9.2 wt% of the total mass of the initial ZnO powder; S3: mixing the precursor powder prepared in S2 with the citric acid solution, grinding and dispersing to obtain a mixed slurry, wherein the amount of the citric acid solution added is 50-100wt% of the mass of the precursor powder; S4: Put the mixed slurry into a steel mold, apply a pressure of 50-300MPa, and cold sinter at 150-300℃ for 0.5-2h; S5: heat treating the cold sintered sample at a temperature ranging from 800 to 950°C for a holding time of 0.5 to 4 hours, and finally obtaining a high-performance ZnO-based varistor ceramic.
2. The method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering according to claim 1, characterized in that: The metal oxide dopant is one or more of Bi2O3, Mn2O3, NiO, SnO2, In2O3, and CaO metal oxides.
3. The method for preparing ZnO-based varistor ceramics based on heat treatment assisted cold sintering according to claim 2, characterized in that: When the metal oxide dopant consists of a plurality of metal oxides, each metal oxide accounts for 0.3-3 wt % of the total mass of the initial ZnO powder.
4. A ZnO-based varistor ceramic, characterized in that: The ZnO-based varistor is prepared by any one of the methods of claims 1-3.
Citation Information
Patent Citations
Method for preparing high-conductivity zinc oxide ceramic at ultralow temperature
CN108546110A
Preparation method of cold sintering-assisted low-temperature densification of Zn3B2O6 microwave ceramic materials
CN114933468A
Ultrahigh-potential-gradient ZnO voltage-sensitive ceramic and low-carbon sintering preparation process thereof
CN115385682A
Method for preparing ZnO voltage-sensitive ceramic by doping in form of soluble salt
CN117303885A
Cold sintering ceramics and composites
US20170088471A1